Successful dying. Later life strategies to cope with the finiteness of life (Sociologisk Forskning, 2020)
This article aims to explore how older people relate to the finiteness of life. Unlike many other similar studies, this study focuses on older people outside palliative care and residential care, those who are still active and engaged in society. When, and in what ways do finiteness of life become apparent to them in their everyday lives? What strategies do they use to manage awareness of the finiteness of life? In 2015, data was collected via six focus group occasions with people aged 69–90. The result show that finiteness of life was something that all respondents were occupied with almost daily and in several ways. In most cases with ambiguity and even fear for the uncertainty of the future, but also with a feeling that the awareness of finitude made the present more valuable. Death was manifested in the respondents’ everyday lives, as something to be postponed, planned and administered by the types of self-disciplining techniques that are significant for successful ageing. I therefore conclude that these norms and techniques of successful ageing have expand into the field of finitude and thereby, become norms and techniques of successful dying.
Keywords: finitude; successful dying; death; successful ageing; later life; ageing